Foundations and Guidelines of a current Tax Code - Tarsitano, Alberto (2016)
The author expose the key points for future tax codification. He recognize the importance of address the legal principles and the dogmatic taxation developed so far, but he warns that they must be of equal importance the new problems have arisen in the area. In addition, he points out the importance of an improvement in the quality of administrative management for the correct application of Tax Law.